2021
DOI: 10.1111/exsy.12716
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge‐based self‐pre‐diagnosis system to predict Covid‐19 in smartphone users using personal data and observed symptoms

Abstract: Covid‐19 is an acute respiratory infection and presents various clinical features ranging from no symptoms to severe pneumonia and death. Medical expert systems, especially in diagnosis and monitoring stages, can give positive consequences in the struggle against Covid‐19. In this study, a rule‐based expert system is designed as a predictive tool in self‐pre‐diagnosis of Covid‐19. The potential users are smartphone users, healthcare experts and government health authorities. The system does not only share the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In the present scoping review, the results of 16 studies identified a positive impact on a diagnosis of COVID-19 with the assistance of CDSS based on ES. 5,17,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In the reviewed studies, rule sets were the most common methods in developing a knowledge base of CDSS. 5,17,88,89,93,94,96,97 Rule-based systems acquire contextual knowledge from extracted data stored and manipulated in other approaches.…”
Section: Knowledge-based Cdssmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present scoping review, the results of 16 studies identified a positive impact on a diagnosis of COVID-19 with the assistance of CDSS based on ES. 5,17,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In the reviewed studies, rule sets were the most common methods in developing a knowledge base of CDSS. 5,17,88,89,93,94,96,97 Rule-based systems acquire contextual knowledge from extracted data stored and manipulated in other approaches.…”
Section: Knowledge-based Cdssmentioning
confidence: 99%
“…101 The reviewed studies extracted data from various sources, such as observed symptoms, specific medical measurements, pre-existing medical conditions or any hospitalization history, recent PCR test results, clinical guidelines, websites (e.g., WHO), and knowledge of experts to develop rule sets. 5,17,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] Therefore, knowledge-based CDSS in these studies can provide a comprehensive view of the patient's health information. This feature enables health practitioners to access treatment recommendations and risk classification, recommend test lists, quickly track test results and symptoms, and access clinical guidelines in the COVID-19 pandemic.…”
Section: Knowledge-based Cdssmentioning
confidence: 99%
“…But for that it is necessary to build time-series dataset with expensive time cost. Another study [6] uses traditional ontology methods to support the analysis and tracking COVID-19 epidemic in Hubei, China. But this method needs the time cost work to build ontology named OntCov19 and its performance to the COVID-19 pandemic has spread fast all over the world, several studies have proposed early triage systems recently.…”
Section: Related Workmentioning
confidence: 99%
“…In this study, they will compare different ontology query languages and query systems, as well as provide user assessments. Elik Ertuğrul et al [4] presented a pre-diagnosis-based knowledge system to anticipate Covid-19 smartphone users using the data and symptoms they have. The technology not only shares user information with specialists butalso analyzes symptoms as atool to analyze potential Covid-19 hazards.…”
Section: Literature Overviewmentioning
confidence: 99%